Sol-Gel Synthesis of Cathode Material MgCoSiO4 for Magnesium Cells - Sun, Jian-Zhi (Asian Journal of Chemistry, 2011)
In present studies, the rechargeable magnesium batteries. MgCoSiO4 was synthesized via sol-gel method and evaluated by TG/DTA, XRD, IR, SEM. The results showed that the product is well-crystalline and gets uniform particle size. Simulation cells were assembled employing the product as positive electrode. Charge/discharge cycle test show that the product present good electrochemical behaviours with discharge capacities 60.5 mAh g-1 after 20 cycles.